Changes in Relative Humidity on Crispness of Dried Sheet Food Produced by Thai Community - Panyoyai, Naksit; Suwannalert, Pilunthasut (Burapha Science Journal, 2026)
Crispness is an important organoleptic characteristic of dried sheet food produced by the Thai communities, such as sticky rice crackers, crisp rice cakes, crispy pork, and crispy fish flakes. Crispness is related to physical factors such as relative humidity, water activity, and moisture content. The objectives of this research were (1) to investigate the standard of community food products and study the structural characteristic at the microscale level of crispness and (2) to study the changes in relative humidity on the crispness. Two mechanical tests, penetration and compression, were performed on samples incubated in relative humidity values of 40%, 50%, and 60% at 30OC. It was found that the ready-to-eat dry products were divided into three groups, rice and flour products, animal products, and the other groups. These sheet-like products had rough surfaces and porous structure. Increasing relative humidity caused more water molecules to bind to the pores resulting in the higher water activity and moisture contents, but lower penetration and compression forces. The decreases of number of peaks and peak heights were clearly observed in the range of relative humidity values of 50-60%. Therefore, to maintain the crispness of some dried food products processed by the communities, the specification of relative humidity value affected to water activity value and moisture content should be considered for their quality control.